Primary cardiac sarcoma with metastases to thyroid and brain - Jyotsna Yesodharan; Subitha Kandamuthan; Usha Poothiode (Wolters Kluwer Medknow Publications, 2015)
Primary cardiac sarcomas are extremely rare with only a few large case series and isolated case reports in the literature. In spite of their aggressive nature with high chances of local recurrence and distant metastases, these tumors and their treatment strategies remain incompletely defined. We report an unsuspected case of primary cardiac pleomorphic undifferentiated sarcoma in a 52-year-old female who presented with progressive dyspnea and palpitation. In the postoperative period, she was detected to have secondaries in brain and thyroid, confirmed thereafter, by fine-needle aspiration cytology.